ANALYSIS OF CONSUMPTION IN A HOTEL IN THE ALGARVE – PORTUGAL, USING BUSINESS INTELLIGENCE TOOLS - Guerreiro, Miguel da Luz (2017)
This article reports on a study carried out with relevant data concerning stock, occupancy and sales forecasts and estimates of revenue for the hospitality industry, analyzing a sample of guests of a four-star hotel located in the Algarve, Portugal, which comprises the fifteen nationalities with the highest occupancy rate during 2014. The aim was to assess the guests’ preferences according to their consumption in the hotel’s restaurants and bars, their room type, their accommodation type, and their travel agency/tour operator, whilst examining the univariate data on the accommodation and consumption expenses in 2014. Based on an analysis and interpretation of the results, it was found that although Portuguese was the nationality with the highest registered number of hotel guests in 2014, the Portuguese spent less than the German on food and beverages in the establishments. On the other hand, the Portuguese were the most regular customers to Restaurant X during the third quarter of the year, and may have spent larger amounts of money on accommodation throughout the calendar year.